Electrochemical route for accessing amorphous mixed-metal hydroxide nanospheres and magnetism. Issue 56 (19th June 2015) - Li, H. B.; Gao, Y. Q.; Yang, G. W.
<x xml:space="preserve">Abstract</x> Amorphous mixed-metal hydroxides nanospheres with a homogeneous distribution of metals in compositions including binary Fe–Co, Fe–Ni and Co–Ni and ternary Ni–Co–Fe hydroxides were prepared via a simple, facile and green electrochemical technique.